Active polyketides isolated from Penicillium herquei - MARINHO,ANDREY M.R. (2013)
In this work we are reporting the isolation by classical methods of chromatography of six polyketides from Penicillium herquei. The compounds citreorosein ( 1) , emodin ( 2) , janthinone ( 3) , citrinin ( 4) , citrinin H1 ( 5) and dicitrinol ( 6) were identified by spectral methods of 1D and 2D NMR and MS. Compounds 1, 2 and 3 were tested against promastigotes forms of Leishmania brasiliensis and 1 and 2 were also assayed against Escherichia coli, Pseudomonas aeruginosa and Bacillus subtilis and showed good activity.